Chitosan ducts fabricated by extrusion-based 3D printing for soft-tissue engineering. (15th May 2020) - Zhao, C.Q.; Liu, W.G.; Xu, Z.Y.; Li, J.G.; Huang, T.T.; Lu, Y.J.; Huang, H.G.; Lin, J.X.
Graphical abstract: Highlights: Chitosan ducts were prepared by three methods based on extrusion and 3D printing. 30 wt.% glycolic acid is optimal based on tensile properties and cytotoxicity. CS slurry possessing shear-thinning properties is very suitable for 3D printing. Mechanical matching with soft-tissue, chitosan ducts can be used for the repairs. Ordered structure gained by self-assembly & liquid-crystal behaviors strengthen CS. Abstract: Three kinds of methods based on extrusion and 3D printing and different acidic solutions (formic acid (FA), acetic acid (AA), glycolic acid (GA) and lactic acid (LA)) were applied for manufacturing the CS ducts. The tensile properties and preliminary cytotoxicity were measured for selecting the optimal ratio of CS slurry. The 3D printability of CS slurry was also studied. The tensile strength, Young's modulus, and fracture strain were tested for evaluating the degree of mechanical matching to soft-tissue. The optimal solvent to CS was 30 wt.% GA solution. The CS slurry possessing shear-thinning properties was suitable for 3D printing. The tensile strength, Young's modulus, and fracture strain of the CS rods were 10.98 ± 0.61 MPa, 12.38 ± 1.19 MPa, and 146.03 ± 15.05 %, correspondingly. The CS ducts manufactured by 3D printing had an excellent mechanical matching to soft-tissue, outstanding biocompatibility and have great potential for soft-tissue restorations.